Efficacy of fipronil against Amblyomma hebraeum ticks on boer goats and detection of Ehrlichia ruminantium in ticks in Limpopo Province, South Africa - Jongejan, Frans (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2018.